International classification of procedures in medicine. - World Health Organization (Geneva : World Health Organization, 1978)
Welke procedures worden er allemaal gevolgd in de medische wereld?
"Published for trial purposes in accordance with resolution WHA29.35 of the Twenty-ninth World Health Assembly, May, 1976."
Includes index.
Keywords: Clinical medicine -- Classification; Medicine -- Classification